UPAYA PENINGKATAN MOTIVASI ORGANISASI KADER POSYANDU DI DESA CABEAN KECAMATAN DEMAK KABUPATEN DEMAK - Sulistyorini, Sulistyorini; Setyarini, Any; Puspitasari, Wahyu (Batara Wisnu : Indonesian Journal of Community Services, 2022)
Posyandu activities are routine activities carried out in all regions in Indonesia, especially in Cabea village. However, so far the posyandu activities in Cabean village have not been effective in accordance with the purpose of establishing the posyandu. Therefore, to increase the effectiveness of posyandu activities in Cabean village, the team from USM provided assistance to motivate posyandu cadres in Cabean village to activate routine posyandu activities. The motivational method used is through assistance in providing material to increase motivation and exposure to the importance of managing motivation. In addition to providing motivational materials and motivation management, the team from USM conducted questions and answers and discussions related to the knowledge of cadres related to posyandu activities in Cabean village. The results of the PKM activities carried out by a team from USM, namely posyandu cadres in Cabean village, greatly appreciated and were motivated to reactivate posyandu activities in Cabean village